2014
DOI: 10.1161/circoutcomes.114.001021
|View full text |Cite
|
Sign up to set email alerts
|

Sex, Socioeconomic Status, Access to Cardiac Catheterization, and Outcomes for Acute Coronary Syndromes in the Context of Universal Healthcare Coverage

Abstract: Background Sex and neighborhood socioeconomic status (nSES) may independently affect the care and outcomes of acute coronary syndromes (ACS), partly through barriers in timely access to cardiac catheterization. We sought to determine whether sex modifies the association between nSES, and the receipt of cardiac catheterization and mortality following an ACS in a universal healthcare system. Methods and Results We studied 14,012 ACS patients admitted to cardiology services between April 18, 2004 and December 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 43 publications
(59 reference statements)
4
50
0
Order By: Relevance
“…The use of area‐level socioeconomic exposures likely represent contextual factors of the physical and social environment such as social position, physical environment, and crime associated with health as opposed to individual‐level characteristics. Reassuringly, however, many previous studies (including some in the jurisdiction that we studied) have shown the prognostic relevance of this area‐level estimation of socioeconomic status in patients presenting with myocardial infarction 3, 6, 20, 22. Consequently, our findings highlight the contextual associations of area‐level socioeconomic factors on access to cardiac catheterization and short‐term mortality in nonmetropolitan ACS patients.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…The use of area‐level socioeconomic exposures likely represent contextual factors of the physical and social environment such as social position, physical environment, and crime associated with health as opposed to individual‐level characteristics. Reassuringly, however, many previous studies (including some in the jurisdiction that we studied) have shown the prognostic relevance of this area‐level estimation of socioeconomic status in patients presenting with myocardial infarction 3, 6, 20, 22. Consequently, our findings highlight the contextual associations of area‐level socioeconomic factors on access to cardiac catheterization and short‐term mortality in nonmetropolitan ACS patients.…”
Section: Discussionmentioning
confidence: 80%
“…Area‐level median household income was determined using postal code information linked to the 2006 Canadian census, as in previous studies 6, 20, 21, 22. Study participants were then divided evenly into area‐level median income quintiles, with the lowest income quintile coded as quintile 1 and the highest area income quintile coded as quintile 5, as in previous studies 6, 9, 14, 20.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, certain epidemiological and behavioral risk factors for MI are risk factors for asthma such as female, 40 non-Hispanic African Americans, 41, 42 low socioeconomic status, 43, 44 or smoking exposure 45 suggesting these factors as are confounders. Other factors such as physical inactivity or obesity 46, 47 as a result of active asthma might be plausible and, in turn, might increase the risk of MI.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies revealed that a higher risk of mortality has been associated with lower SES in the setting of ACS [33]. This is because of obstacles to in-time medical care and settled appropriate interventions [34].…”
Section: Resultsmentioning
confidence: 99%